Исследование собственных и примесных точечных дефектов в сапфировых подложках люминесцентными методами - Bletskan, D. I.; Pekar, Ya. M.; Lukyanchuk, A. R. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
This work is devoted to the study of intrinsic and impurity point defects in sapphire substrates and raw materials using luminescence methods. It is proposed to employ luminescence under various types of excitation as a sensitive and informative rapid technique for detecting intrinsic and impurity point defects in sapphire crystals and substrates.